Modelling of Chemical and Magnetic Order in Ni-Mn-Al Shape Memory Alloys Using Monte Carlo Simulations - Alés, Alejandro (2022)
A model for the description of atomic and magnetic ordering in Ni − Mn − Al shape memory alloys is presented. The energetic parameters for the chemical and magnetic interactions are estimated from fitting to experimental data. Monte Carlo simulations based on this model correctly reproduce the critical B2 ↔ L21 ordering temperatures as a function of composition for three pseudobinary composition lines, as well as the nature of the low temperature magnetic transition.A ferromagnetic configuration is predicted for alloys in the stable L21 structure, whereas an antiferromagnetic state is obtained for metastably retained B2 order; this is in agreement with experimental observations. It is found that atomic ordering is mainly governed by Ni − Al interactions, and that the formation of B2 order can delay stabilization at low temperatures of the L21 configuration; the magnetic type of ordering depends on the Mn − Mn distance.